Ozonation Treatment, Edible Coating Carrageenan, and Temperature Variation on The Quality of Fresh-Cut Pineapple During Storage - Maulidiyah, Alifah; Darmawati, Emmy; Widayanti, Siti Mariana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Fresh-cut pineapples are increasingly popular in Indonesia, but it damage easily due to contamination of pathogenic microorganisms, resulting in a short shelf life. This research aims to examine the effect of applying ozone and edible carrageenan coating on the quality of fresh-cut pineapple stored at low temperatures. The experiment used factorial completely randomized design. The first factor was concentration of carrageenan and the second factor was storage temperature. Based on the lowest TPC (total plate count) value from a preliminary research, the experiment was conducted with soaking time of 60 s. Results showed that weight loss, hardness, and TDS values was respectively 2.24 %; 13.03 °Brix; 11.42 kgf, and tended to increase until the last day of storage. The best results was found at 2.5% carrageenan coating and 5 °C. Results from the organoleptic test, however, found the highest score of 4.41 was collected from 1.5% carrageenan coating and 5 °C. It can be concluded that the combination of soaking in ozonized water for 60 s, immersing the fruit in a 2.5% edible coating carrageenan solution stored at 5 °C can maintain the quality of the fruit and increase the shelf life of fresh-cut pineapple compared to controls that were not given any treatment. Keywords: Drying, Physical Quality, Temperature, Tomatoes, Tween 80.